2019
DOI: 10.20937/rica.2019.35.02.18
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the Differential Pulse Anodic Stripping Voltammetry Method With a Hanging Mercury Electrode for Thallium (I) Determination in the Presence of Lead (Ii) and Copper (Ii) for Application in Contaminated Soils

Abstract: Optimizacion del método voltamperómetrico de redisolución anódica de pulso diferencial con un electrodo colgante de mercurio para la determinación de talio [I] en presencia de plomo [II] y de cobre [II] para su aplicación en suelos contaminados)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Cruz‐Hernández et al. [30] indicated that the amount of thallium in the soil can range from 0.05 μg g −1 to 3.2 μg g −1 , while Łukaszewski and Zembrzuski [31] estimated the thallium content in soil samples at the level from 0.1 μg g −1 to 0.56 μg g −1 . In this study, the obtained thallium(I) value of…”
Section: Discussionmentioning
confidence: 99%
“…Cruz‐Hernández et al. [30] indicated that the amount of thallium in the soil can range from 0.05 μg g −1 to 3.2 μg g −1 , while Łukaszewski and Zembrzuski [31] estimated the thallium content in soil samples at the level from 0.1 μg g −1 to 0.56 μg g −1 . In this study, the obtained thallium(I) value of…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an electrochemical technique for heavy metal detection was developed using a hanging mercury drop electrode (HMDE) 87 or a thin film mercury electrode 88 . However, mercury is environmentally toxic, and mercury poisoning causes prominent nervous system effects 89 .…”
Section: Introductionmentioning
confidence: 99%